PRODUCTION AND FUNGICIDAL ACTIVITY ASSESMENT OF WOOD-WASTE LIQUID SMOKE - Rahmat, Budy; Natawijaya, Dedi; Surahman, Endang (International Journal of Research -GRANTHAALAYAH, 2020)
Liquid smoke is known to contain compounds that can control plant disease pathogens. This study aims to produce wood-waste liquid smoke and determine its effectiveness as a fungicide on plant pathogens. This research was conducted in two experimental stages, namely: (i) in vitro test as a preliminary test of the effectiveness of teak waste liquid smoke at concentrations of 0, 0.5, 1, 1.5, 2, and 2.5%; and (ii) in vivo test was arranged in randomized block design consisting of seven levels of liquid smoke concentration, namely 0, 1, 2, 3, 4, 5, and 6%, each of which was repeated four times. The results showed that the pyrolysis of 1 kg of wood waste was produced with the proportions of liquid smoke, charcoal and tar, respectively: 312 mL, 31 g, 367 g and the uncondensed gases. Treatment of liquid smoke in the in vivo test showed that a concentration of 1 to 2.5% liquid smoke was able to suppress the growth of the pathogenic fungus Sclerotium rolfsii 100%. The treatment of liquid smoke in the in vivo test showed an effect on inhibition of the growth diameter of fungal colonies, suppressing the disease occurance, and suppressing the lesion diameter.